Evidence for the involvement of TNF-α and IL-1β in the antinociceptive and anti-inflammatory activity of Stachys lavandulifolia Vahl. (Lamiaceae) essential oil and (-)-α-bisabolol, its main compound, in mice - Barreto, Rosana S.S.; Quintans, Jullyana S.S.; Amarante, Ruthy K.L.; Nascimento, Tainá S.; Amarante, Rosana S.; Barreto, André S.; Pereira, Erik W.M.; Duarte, Marcelo C.; Coutinho, Henrique D.M.; Menezes, Irwin R.A.; Zengin, Gokhan; Aktumsek, Abdurrahman; et al. (Journal of ethnopharmacology, 2016)
Stachys lavandulifolia Vahl (Lamiaceae) is a medicinal plant widely used in Turkey and Iranian folk medicine due to its analgesic and anti-inflammatory properties, but little is known about its essential oil. We studied the antinociceptive and anti-inflammatory effects of S. lavandulifolia essential oil (EOSl) and (-)-α-bisabolol (BIS), its main compound, in algogen-induced orofacial nociceptive behavior in mice, and assessed the possible involvement of pro-inflammatory cytokines in these profiles. The GC-FID and GC–MS analysis of EOSl demonstrated the presence of (-)-α-bisabolol (56.4%), bicyclogermacrene (5.3%), δ-cadinene (4.2%) and spathulenol (2.9%) as the main compounds. Male Swiss mice were pretreated with EOSl (25 or 50mg/kg, p.o.), BIS (25 or 50mg/kg, p.o.), morphine (3mg/kg, i.p.) or vehicle (saline 0.9% with two drops of tween 80, 0.2%), before formalin- (20μl, 2%), capsaicin- (20μl, 2.5µg) or glutamate- (20μl, 25Mm) injection into the right upper lip (perinasal area) in mice. The anti-inflammatory profile of EOSl or BIS (50mg/kg) was assessed by the inflammatory response induced by carrageenan (2% in 0.2mL) in mice (pleurisy model). Our results showed that p.o. treatment with EOSl and BIS displayed significant inhibitory (p<0.05 or p<0.01 or p<0.001) effects in different orofacial pain tests on mice, but BIS proved to be more effective, significantly reducing nociceptive behavior in all tests including both phases of the formalin test. The analgesic effect is not related to any abnormality since EOSl- or BIS-treated mice exhibited no performance alteration in grip strength. Moreover, EOS1 and BIS exhibited a significant anti-inflammatory effect (p<0.001) in the pleurisy model of inflammation, which seems to be related to a significant reduction (p<0.05) of the pro-inflammatory cytokine TNF-α in BIS treatment, and of the pro-inflammatory cytokine IL-1β (p<0.01) in EOS1 treatment. Our results corroborate the use of S. lavandulifolia in traditional medicine as an analgesic and anti-inflammatory, which seems to be related to (-)-α-Bisabolol, the main compound of EOSl. [Display omitted]